Ideologia jurídica e conflitos fundiários - Moreira, Márcio Alan Menezes (2012)
The urban land conflicts are one of the main problems of large Brazilian cities. Erected on a dual development in poverty and income concentration, witnessed a consolidation of a city segregated social classes increasingly hostile camps, especially with regard to access to urban land. These conflicts eventually ending up in the Judiciary, which eventually becomes a space resolution (also) political problems concerning public policies that the State is unable to solve. However, in its activity, several factors affect decisions about the cognitive activity of the judge. All their moral, religious, and cultural permeates the act of judging. In this paper we focus on a specific element of the trial: legal ideology. Thus, it is important to realize the judiciary within the state system, from a particular theoretical framework that allows us the analysis of capitalist society and its intersections with the law. We identify the existence of an ideology that has legal as referring to the appearance of social relations, distorting reality, contributing to the reproduction of capitalist relations. In this way, the judiciary, even immersed in this hegemonic ideological content, you can apply in cases of land conflicts, a range of remedies, from the legislation constitutional and infra. At this point, then there is a conflict between fundamental rights: the right side of the property and the other the right to housing. Finally, we analyze a case study, ten lawsuits of land conflicts in Fortaleza, seeking to identify the ideological elements that make the decisions.